TINJAUAN YURIDIS PERLINDUNGAN KONSUMEN MUSLIM DALAM MENDAPATKAN JAMINAN PRODUK HALAL TERHADAP PEMBELIAN SECARA ONLINE - Fadzlurrahman, Fadzlurragman; Suparto, Susilowati (Fakultas Hukum Universitas Bangka Belitung, 2019)
In 2019, the Indonesian government will target all products circulating in halal-certified Indonesia. While the readiness of the Halal Product Guarantee Agency (BPJPH) is still constrained by a Government Regulation that has not been approved by the President. The development of technology and information makes buying and selling transactions can be done online, there are many products sold online, some of which do not include halal labels in their products. Seeing the inequality between das sollen and das sein, this article formulates the problem of how to guarantee legal protection for the sale of non-halal labeled products sold online as well as any obstacles that must be anticipated by the JPH Law to protect Muslim consumers from obtaining halal products in electronic transactions using normative research method.